Implementasi Kebijakan Sistem Peradilan Pidana Anak di Wilayah Hukum Polres Morowali Utara - Risupal, Theodorus; Hattab, Syahruddin; Mangngasing, Nasir (CV. Rayyan Dwi Bharata, 2025)
This study aims to determine the implementation of Juvenile Criminal Justice System Policy in the Jurisdiction of the North Morowali Police Department. This study uses qualitative data collection methods. The research location is at the North Morowali Police Department Office. The theory used in this study is the theory put forward by George C. Edward III. Nine informants participated in this study. Data were obtained from observations, interviews, and documentation. The data analysis methods include data collection, data condensation, data presentation, and conclusion drawing/verification. The results of the study on the Implementation of the Juvenile Criminal Justice System Policy in the North Morowali Police jurisdiction indicate that its implementation has not been optimal. The four main aspects of policy implementation communication, resources, disposition, and bureaucratic structure show varying results. The communication aspect is considered quite good, as coordination between law enforcement officers and related agencies in handling juvenile cases has begun to be established, although there are still obstacles in the delivery of information and understanding of the policy at the implementing level. The resource aspect is considered less good, due to the still limited number and competence of officers with specific understanding of the juvenile criminal justice system, as well as the lack of supporting facilities and infrastructure such as special rooms for examining children or psychological assistance. The disposition aspect is also not good, as evidenced by the still weak commitment, attitude, and integrity of some officers in prioritizing the principles of restorative justice over a repressive approach. Meanwhile, the bureaucratic structure aspect is considered quite good, because there are already mechanisms and SOPs for handling juveniles that are clearly regulated, but still requires improvement in cross-agency coordination and consistency of implementation in the field.